(untitled) (Texas Journal of Agriculture and Biological Sciences, 2025)
In the diverse soil and climatic conditions of irrigated agriculture in Uzbekistan, in connection with global climate change and soil degradation, improved technologies for the use of mineral fertilizers have been developed and are an urgent task. In addition, at present, in almost all zones of irrigated agriculture of the republic, mineral fertilizers are applied to winter wheat according to the Agro recommendations prepared earlier [1;31-33, 2;37-41, 3;35]. To obtain guaranteed and planned yields of winter wheat, it is necessary to conduct zonal experiments to study the responsiveness of winter wheat to mineral fertilizers, in particular in the meadow gray soils of the Navoi region